Progress Report on the First Five-Year Plan for Bombay State (1954-55 and 1955-56) - Planning Commission (Planning Commission, 1954)
The two years which comprise the period of this Progress Report witnessed the Indian economy emerging with added strength and stability. The outlay of the National Plan was enlarged considerably in the third year of the Plan and it was possible to step up the level of expenditure substantially to about 2 1/2 times the level in 1951-52. Over the five years the aggregate outlay in the public sector is expected to be a little below Rs. 2,000 crores that is about the level envisaged when the National Plan was finalised in 1952.
Government of Bombay, Political and Services Department